Flood Insurance as a Flood Management Tool: An Economic Perspective - Tun Lin; Franklin D. De Guzman; Maria Cita Cuevas (Asian Development Bank (ADB), 2007)
Flood insurance is an insurance contract that covers losses to properties caused by flooding. Although floods affect Asia more than any other continent in the world, flood insurance is still at its nascent stage in the region. This paper explores the potentials and challenges of adapting flood insurance to the Asian setting. Due to the need to explore alternative flood management schemes and the context-specificity of flooding, country-specific design and testing of a feasible flood insurance is deemed necessary. This paper presents key aspects of flood insurance including economic design issues.
hdl:11540/1861
Keywords: 330; Humanitäre Hilfe; Überschwemmung; Asien